Nature as a Place to Meet God - Maciej Ostrowski (Nicolaus Copernicus University in Toruń, 2011)
The author of the article draws the reader's attention to the components of the natural world, which let us discover the existence of God the Creator. Beauty is suggested to be the most important of these components. Beauty resides in the perfection of the object observed, its proportions and harmony, variety and order, glamour, grace, majesty and grandeur. Unfolding the mystery of life itself is also conducive to the recognition of God, especially in the silence of nature and being surrounded by the scents it exudes. However, the very contact with nature is not enough to encounter God. The author of the article contemplates the ways of educating people which may facilitate their discovery of God in nature. It is necessary to teach man how to contemplate the surrounding world. Careful observation, concentration on the object, calming down, leaving the hustle and bustle behind are indispensable to learn this, as well as the ability to describe your own feelings and the rejection of the utilitarian attitude to the world. The author makes reference to biblical texts, thoughts presented in papal speeches and private observations.